O AGENDAMENTO DE TELEJORNAIS BRASILEIROS EM SITES NOTICIOSOS DE CONTEÚDO COLABORATIVO - SAAR, Claudia Maria Arantes de assis (2016)
The thesis investigates if with the free news production, people who post information on collaborative content sites, known as interacting, tend to reproduce information that was scheduled for Tv news. This study is a comparison of the collaborative content vehicles Vc reporter, Vc no G1 and Eu reporter with TV news SBT Brasil, Jornal Nacional, Jornal da Record and Jornal da Band. We sought to determine whether those newscasts guide the collaborative platforms. The hypothesis assumes that Brazilian TV news have been building over time a credible relationship with the viewer, so it is possible to think that the interacting use the same criteria for selecting the broadcasts and reproduce similar information in collaborative content sites. The method used was content analysis, based on the study of Laurence Bardin and the type of research used was quantitative. This research concluded that, within a small portion of the universe surveyed, there are schedules of television news across the collaborative content